Transformation of Rural Communities in Parigi Moutong Regency - Alimuddin (International Journal of Science and Society, 2023)
The purpose of this research is to find out about the process of transforming rural communities, forms of multi-actor intervention in rural transformation construction and new capacities for rural development in Parigi Moutong. This type of research is research using a qualitative research method approach as a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. This approach is directed at the setting and the individual holistically (whole), in this case individuals or organizations cannot be separated into variables or hypotheses and need to view them as part of a whole. The results showed that in the process of community transformation underwent two categories, slow and fast, which were conditioned by several of them: 1) socio-cultural background factors, 2) economic factors of property ownership, 3) political factors of power. Technological factors in the utilization of production resources. The form of intervention is seen in the community itself which is related to their daily lives with work ethic capital, government and entrepreneurs who have interests. The transformation process still has a gap between the indigenous population and the immigrant population.